Meningkatkan Kemampuan Keterampilan Bahasa Anak dalam Lembaga Pendidikan Islam - Titin Mariatul Qiptiyah (Al-Riwayah : Jurnal Kependidikan, 2022)
Abstract : The background of this research is that the activities of developing children's language skills are interesting and not boring, as teachers must be clever in packaging learning activities according to the principle of playing while learning and learning while playing. Research focus What are the teacher's efforts in improving children's listening, speaking and reading skills?. The research method uses a qualitative approach. The results showed that the language skills achieved by the students of group B PAUD Nurul Yaqin Sukoreno Village were more improved compared to before after conducting research practice through the activity of the fairy tale storytelling method "the mouse deer and the crocodile" using serialized picture media. Likewise, teachers find it easier to convey storytelling methods, and provide fun learning.